Renewable Energy Sources - Benefits and Drawbacks From the Perspective of the Experiences of China, Brazil, Canada and the United States - Nartowska, Edyta; Rozenvalde, Alina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article was to identify actions, based on the experiences of China, Brazil, Canada, and the United States, that countries can implement to increase the share of hydro, solar, and wind energy in their economies. The analysis relied on a literature review and data obtained from the Our World In Data database. The findings indicate that there are effective strategies for clean energy adoption that can be applied worldwide.
Keywords: hydropower; solar energy; wind energy; renewable energy; climate changes; sustainable development